Experimental Study on Mechanical Properties and Seepage Laws of Raw Coal under Variable Loading and Unloading Rates - Kangwu Feng; Kequan Wang; Dongming Zhang; Yushun Yang (Geofluids)
This manuscript studied the effects of variable axial pressure loading rate and variable confining pressure unloading rate on the deformation behavior and seepage characteristics of raw coal under alternate loading and unloading of axial pressure and confining pressure. It believed that as axial stress increases, axial strain ε1 decreases, radial strain ε3 increases, and permeability k decreases, and ε1′, ε3′, and k′ increase when confining pressure is decreases. With the loading of axial stress and the unloading of confining pressure, the variation amplitudes of ε1′, ε3′, and k′ values reduce gradually. During axial stress loading, the rise in the amplitude of ε1 is larger than that of ε3 and the reduction in the amplitude of k, indicating that ε1 is more sensitive to axial stress than ε3 and k. During unloading of confining pressure, the increase rate of ε3 is larger than that of ε1 and k; also, ε3 showed a high sensitivity to confining pressure. In the stage of axial stress loading and confining pressure unloading, the evolution law of deformation and permeability parameters is basically consistent with the change in loading and unloading rate.